Incomplete-Information Capital Market Equilibrium with Heterogeneous Expectations and Short Sale Restrictions - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1996)
This article extends Merton's (1987) asset-pricing model under incomplete information to consider the situation when investors' beliefs are divergent and short selling is restricted. The article finds that the diversity of beliefs increases the mean variance inefficiency of the market portfolio and the shadow cost of information. However, the inefficiency of the market portfolio due to divergent beliefs is mitigated by short-sale restrictions. The article also finds that the effect of firm size is intertwined with the residual return variance risk. Consistent with the findings of Levy (1978) and Carroll and Wei (1988), the residual return variance plays an important role in determining the risk and risk premium of each security. Finally, the shadow cost of information is larger and the equilibrium security return is higher when expectations are more diverse. And the effects of divergent beliefs on both information cost and required rates of returns are negatively related to the relative size of investor base for a particular security.